Empowerment components related to smoking prevention among male students: A cross-sectional study - Naser Sharafkhani; Mehrnoosh Jasemzadeh; Mostafa jiba; Leili Rabiei; Arash Salahshouri (Clinical Epidemiology and Global Health)
Background: Smoking is one of the unhygienic behaviors in human societies and unfortunately, its increasing prevalence among all classes especially students as effective role models in society, has caused many concerns. This study aimed to investigate the components of empowerment in connection with the adoption of smoking prevention behaviors (SPB) in male students at Azad University of Ahvaz. Methods: The present study was of a descriptive-analytical type, which was conducted with the participation of 315 male students between 2021 and 2022. Sampling was stratified-random. The data collection tool of this study was a questionnaire containing demographic characteristics and questions related to various empowerment components concerning smoking prevention and the adoption of SPB. The data were analyzed using descriptive and inferential statistical methods, including prevalence, mean, standard deviation, Pearson's correlation coefficient, and linear regression, using SPSS 22 software. Results: The results of this study showed that 18.06 % of the students were active smokers while 75.88 % of them had smoking experience. Also, the results of the study showed that among the components related to empowering students about smoking prevention, self-efficacy, negative attitude towards smoking, social support, self-esteem, and anti-smoking policies were the most important predictors of smoking behavior with a change variance of 39.5 % (R2 = 0.395). Conclusion: Considering the unaffordability of the average score of adopting SPB among the students, the necessity of designing and implementing interventions to improve the student's abilities in smoking prevention is greatly felt.